Testowe badania efektywności systemowego nauczania i uczenia się literatury = The Test Researches of the System Teaching Effectiveness and of Literature Learning - Błażewicz, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
School achievement tests, quite different from the traditional knowledge tests were applied to the primary school pupils. In Rzeszów ten classes of pupils from the eighth grade who had been taught according to the system teaching, and the same number of pupils from Wrocław where the system teaching had not been used were tested. The researches prove the system teaching to be superior to the conventional (traditional) one.
Keywords: dydaktyka literatury; badania; efektywność